Twenty nail dystrophy: A feature of direct nail apparatus involvement in leprosy - Ashish Kumar Nayak; Biswanath Behera; Siddhartha Dash; Madhusmita Sethy; Aparna Palit (Wolters Kluwer Medknow Publications, 2022)
Lepromatous leprosy (LL) is a systemic illness which involves various organs either directly due to Mycobacterium leprae or as a part of lepra reaction. Nail changes occur in leprosy with variable frequency but may not have a direct causal relationship with leprosy. Hereby, we are describing a case of untreated LL presenting with twenty nail dystrophy and a direct causal relationship of the same due to M. leprae.